Proofs and Research Programmes: Lakatos at 100 (Springer Nature, 2025)
This open access book offers new insights into issues raised in philosophy of mathematics and in philosophy of science by Imre Lakatos. Lakatos was one of the most significant philosophers of the 20th Century, and his ideas remain important and relevant today. November 2022 saw the centenary of Lakatos’s birth, and the event was marked by an international conference held at the LSE – where Lakatos made his career after he had emigrated from Hungary to England. This volume consists of a selection of papers presented at the conference along with two additional contributions to debates about Lakatos’s continuing influence and importance.